2012
DOI: 10.1002/dev.21009
|View full text |Cite
|
Sign up to set email alerts
|

Early maternal care predicts reliance on social learning about food in adult rats

Abstract: Many vertebrates rely extensively on social information, but the value of information produced by other individuals will vary across contexts and habitats. Social learning may thus be optimized by the use of developmental or current cues to determine its likely value. Here, we show that a developmental cue, early maternal care, correlates with social learning propensities in adult rodents. The maternal behavior of rats Rattus norvegicus with their litters was scored over the first 6 days postpartum. Rat dams s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 43 publications
4
36
0
Order By: Relevance
“…Therefore, across the full range of conditions that might be thought to induce dissatisfaction or uncertainty, these intuitive, folk psychological labels may provide poor predictors of the magnitude of social learning effects. Illustrating this point, Lindeyer et al [12] recently found that, in adulthood, rats that had received relatively little licking and grooming from their mothers (low LG) showed weaker socially enhanced food preferences than rats that had received more licking and grooming (high LG). As the authors pointed out, previous research has indicated that low-LG rats are more risk-sensitive and anxious-at an intuitive level, they are more 'uncertain'-than high-LG rats.…”
Section: Copy When Alternative Unsuccessfulmentioning
confidence: 96%
“…Therefore, across the full range of conditions that might be thought to induce dissatisfaction or uncertainty, these intuitive, folk psychological labels may provide poor predictors of the magnitude of social learning effects. Illustrating this point, Lindeyer et al [12] recently found that, in adulthood, rats that had received relatively little licking and grooming from their mothers (low LG) showed weaker socially enhanced food preferences than rats that had received more licking and grooming (high LG). As the authors pointed out, previous research has indicated that low-LG rats are more risk-sensitive and anxious-at an intuitive level, they are more 'uncertain'-than high-LG rats.…”
Section: Copy When Alternative Unsuccessfulmentioning
confidence: 96%
“…Three studies, all with rats, show that maternal 142 deprivation or markers of high maternal stress (infrequent licking and grooming) reduce the 143 subsequent social learning of food preferences from unfamiliar demonstrators [52][53][54]. This 144 facultative switching in response to specific developmental cues might represent an adaptively 145 limited degree of phenotypic plasticity: maternal deprivation or stress might indicate a recent 146 environmental shift to which mothers are poorly suited, making it adaptive to rely less on others' 147 potentially out-dated knowledge (although see [55] for caution regarding anticipatory parental 148 effects).…”
Section: Developmental Stress or Deprivation 140mentioning
confidence: 99%
“…Recent studies have shown that social learning in rats can be influenced by early developmental cues such as maternal care (Lindeyer et al 2013), and in bees by past learning histories (Dawson et al 2013). However, while similar processes may well operate in humans (Heyes 2012), it is difficult to explain the species differences in cumulative cultural evolution described above without positing some kind of genetic adaptation in the human lineage, perhaps involving the extent of imitation during childhood (Lyons et al 2007) or theory of mind (Tomasello et al 2005).…”
Section: Are Social Learning Biases Learned or Innate?mentioning
confidence: 99%